Penerapan Dashboard Keuangan Berbasis Spreadsheet untuk Monitoring Kinerja UMKM: Konveksi Eva-Evi - Muhammad Rizqi Fahriza; Sherena Wahyutari; Dika Puspitaningrum; Nadhia Citra (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service activity aims to help the Eva-Evi Convection MSME improve its financial management capabilities through the implementation of a spreadsheet-based financial dashboard. The main problems faced by partners are manual, unstructured financial records, and the mixing of business and personal finances, making it difficult to monitor business conditions. The method used is a needs-based participatory approach through the stages of problem identification, designing a Google Sheets-based financial dashboard, training in spreadsheet usage, implementation assistance, and monitoring and evaluation. The results of the activity show that partners are able to understand the basic concepts of financial management, record transactions more systematically, and utilize the dashboard to integrate income, expenses, and business profits. The implementation of this dashboard is considered effective in supporting more appropriate business decision-making and has the potential to become a simple digitalization model for other MSMEs.